Mechatronics engineering projects: theory and applications - Toha, Siti Fauziah; Abdul Muthalif, Asan Gani; Mahmood, Iskandar Al-Thani (s.n, 2012)
The Mechatronics engineering program at the faculty of engineering, International Islamic University Malaysia (IIUM) was established in 1994. It came into existence as a full-fledged department in 1998. Ever since its establishment, the department has produced the largest number of engineering students from IIUM and has been renowned as one of the best Mechatronics Engineering Department in Malaysia